Risk factors and drug resistance of non-tuberculous mycobacteria in HIV/AIDS patients: a retrospective study in southern China - Ye, Jing; Yang, Qingpeng; Huang, Yan; Lin, Mei; Xian, Xiaomin; Huang, Liwen; Qin, Huifang; Zhou, Chongxing; Zhang, Yingkun; Liang, Xiaoyan; Ou, Jin; Cui, Zhezhe (Frontiers in Public Health, 2025)
BackgroundThe incidence and infection rate of Non-tuberculous Mycobacteria (NTM) are increasing across different regions, with regional variations in the types, distribution, and drug resistance profiles. Our objective was to investigate the risk factors, distribution of predominant Mycobacteria species, and phenotypic drug resistance profiles in co-infected HIV/AIDS patients in southern China.MethodsBlood and sputum samples were collected from 2,985 HIV/AIDS patients without prior history of pulmonary tuberculosis (PTB) in five designated hospitals in Guangxi, southern China from January 2019 to December 2020. Univariate analysis and binary logistic regression models were used to explore the related risk factors of HIV/AIDS patients with NTM infection and those with Mycobacterium tuberculosis (MTB) infection, respectively. Interferon-γ release assay (IGRA) tests and CD4+ counts were performed on blood samples, Roche medium was used for sputum culture, and positive isolates underwent species identification and drug susceptibility testing.ResultsMycobacterium tuberculosis and NTM culture positivity rates were 1.2% (35/2985) and 2.2% (66/2985), respectively (χ2 = 9.679, p = 0.002). Predominant NTM pathogens were Mycobacterium avium (28.8%, 19/66), Mycobacterium fortuitum (21.2%, 14/66), and Mycobacterium chelonae/abscessus complex (16.7%, 11/66). Multivariate analysis revealed cough (Adj. OR: 192.47, 95%CI: 15.71–2357.63, p < 0.001) and farming (Adj. OR: 20.92, 95%CI: 1.33–328.93, p = 0.031) as risk factors for NTM co-infection, whereas other pulmonary symptoms increased risk of MTB infection (Adj. OR: 3.37, 95% CI: 1.03–11.08, p = 0.045). Cough significantly differed between NTM and MTB groups (χ2 = 66.070, p < 0.001). Sixty-six NTM strains were tested for resistance to 10 common antibiotics. The drug resistance rates of para-aminosalicylic acid (PAS), Isoniazid (INH), Levofloxacin (LFX), Kanamycin (K), Ethambutol (EMB), Capreomycin (CPM), Rifampin (RFP), Moxifloxacin (MFX) and Amikacin (AM) exceeded 50.0%., while Protionamide (TH1321) was 25.8%. There was no significant in interferon status distribution across CD4+ counts groups (p = 0.574).ConclusionFor HIV/AIDS patients presenting with cough symptoms, it is recommended that molecular biology techniques be employed concurrently with MTB testing to screen for and identify NTM, thereby clarifying the specific type of mycobacterial infection present. IGRA cannot completely distinguish MTB from NTM, and more auxiliary examinations are needed.